Influência da idade e do sexo sobre o perfil bioquímico sérico de jumentos da raça brasileira - Alves, Lorenna Marques Dias (2008)
24 serum constituents were dosed from 102 Brazilian donkeys, to compare with values obtained for other authors to other races of equines and to verify if the age and the sex influence in these values. Of the animals, 77 were male and 25 females; It had been also grouped by age: 0-6 months (38 animals), 7-12 months (29 animals), 13-18 months (28 animals) and more than 18 months (13 animals). After the dosages, were made the statistical analysis by the test of Tukey 5% and compared the values of the different groups. The majority of the values was in accordance with the results considered for other authors, few differences had been found. Statistical differences between males and females had been found, only for magnesium, GGT (gamma glutamiltransferase) and urea; however, in relation to the age, significant differences for the majority of the constituent had been found, mainly for the young, enclosed animals in the age band of 0 the 6 months. Amongst the 24 analyzed constituent, the only ones that they had not presented variations related to the age had been the urea and the ionized calcium. The results that were different from the other authors can be related to the race, ambient influences, amongst others. The values of the sanguine constituent had not been differed significantly between the sex; however, it is noticed that the age intervenes considerably with the values of total proteins, albumen, globulin, relation albumen: globulin, creatinine, urates, cholesterol, triglicéris, match, total calcium, relation calcium: match, Mg (magnesium), chlorides, sodium, potassium, AST (aspartate aminotransferase), ALT (alanine aminotransferase), GGT and CK (creatine kinase). The observed variations are given that they can serve of base for accomplishment of new research involving Brazilian donkeys and contribute for the creation of exclusive values of reference to this race.